Plasmonic substrates for ultrasensitive surface-enhanced Raman spectroscopy: application to the detection of food toxins - Oliveira, Maria João Quitoles De (2018)
The food contaminants consist in chemical substances in food products. The contaminants include for example, pesticides, antibiotics, and toxins. Recently there has been an increasing concern in detection of such contaminants not only for the prevention of public health, but also of the environment. The currently available methods for detection of chemicals in foods are time consuming, expensive and complex to operate. Hence, is necessary to development other methods to overcome the aforementioned disadvantages. The main objective of this work was to explore the feasibility of surface-enhanced Raman spectroscopy (SERS) as a sensitive, robust, simple and fast technique for the detection of food contaminants. Therefore, two different types of SERS substrate were developed. One of the substrates had paper as solid support matrix, with wells enclosed by hydrophobic barriers (two paper types were studied, chromatography and office). Nanoparticles (NPs) of silver, spherical and star-shaped, were chemically synthesized and deposited in the wells by drop-casting. The SERS efficiency study highlighted the office paper as the most appropriate support, due to the greater retention of NPs in star-shape on its surface. The detection limit values (LOD) and quantitation (LOQ) for rhodamine 6G (R6G) were 0.17±0.04 and 2.5±0.5 ppb, respectively. This substrate has proven reproducible and stable over time (5 weeks) with relative standard deviations (RSD) of 1.7 % and 7.3 %, respectively. The second substrate was made by physical vapor deposition (PVD) allowing a layer of spherical NPs. The LOD and LOQ values for R6G were 0.015±0.002 and 1.1±0.2 ppb, respectively. The proof-of-concept study was conducted with malathion and domoic acid (DA) and was not possible to detect DA. However, the LOD and LOQ for malathion in paper SERS substrate were ≈3944 and ≈1652 ppm respectively, and for the PVD substrate were, ≈925 and ≈5644 ppm, respectively. Both SERS substrates and their production method, were sensitive, robust, and inexpensive, allowing the rapid detection of analytes.